Development of GUI for image repair and restoration - Siak, Ru Ren (2015)
The GUI for the image repair and restoration is designed to be a one stop solution to repairing and restoring old photographs back to its full glory. It emphasizes the need for an easy to use and effective solution to run basic image processing techniques in a simple program. The system is about enhancing the efficiency regarding image repair. Without an existing one stop image repairing software in the market, the algorithm written for this study is one that moves into the forefront in the field of image repair. The current solution is to use an image editing software like Adobe Photoshop. Novice users may find it difficult and sometimes frustrating to go through the different functions and tools provided by Adobe Photoshop. However, there are some considerations to be taken into account when using the GUI offered by the algorithm is this study. Further assessment in the feasibility in employing shape recognition techniques in this study is to be carried out. Shape recognition is an important factor in all of image repair. It is a profound and abstract study. The results revealed that the repaired image always resulted in the image to be darker than the original image. Most of the ambient noise in the image concerned can be removed. The algorithm written is tasked to solve this problem and with further improvements, it is possible to offer a complete solution to Image repair and restoration.